Study Of Some Biochemical Parameters in Dose During Pregnancy in Goats - Faisal, Huda T.; Abid, Mohammed Kadhem; Abed, Aamir.M. (Journal of Advanced Zoology, 2022)
This study was made to study the level of biochemical parameters presence in pregnant and non-pregnant goats from middle east. The level of S. glucose, S. urea, S. creatinine, S. cholesterol, and S. triglycerides were determined and analysed using analysis of variance software at P-Value of P<0.05, which showed insignificance difference between the pregnant and non-pregnant goats. Other biochemical parameters determined and analysed in this work include S. total protein, S. albumen and S. globulin. The level of these parameters between pregnant and non-pregnant is in significance and therefore, looks similar. S. calcium, S. potassium and S. sodium minerals were also determined and analysed using the same method as mentioned above. The obtained results demonstrated that there is no significance difference between the pregnant and non-pregnant goats in terms of the level of some biochemical parameters